IMPLEMENTASI PENGEMBANGAN KARIER OLEH GURU BK DALAM MEMPERSIAPKAN SISWA HINGGA PENENTUAN PILIHAN KARIER DI MA SIMBANG KULON PEKALONGAN - Rahma Nafalina Azzahra; Muntaqo Fadli; Aulia Irmiati, Rahma; Maulana Nur Yasin; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the important role of Guidance and Counseling (BK) teachers for Madrasah Aliyah (MA) students in providing career information, providing individual and group guidance, and determining career choices that suit their interests and talents. However, students still face various challenges in choosing a career. Some students experience confusion in determining careers and further education majors that suit their interests, talents, and abilities, lack understanding of their potential, lack of information about educational and job prospects, and are influenced by the opinions of family and peers. This study aims to describe the implementation of career development carried out by BK teachers in preparing students to determine career choices at MA Simbang Kulon Pekalongan. This study uses a qualitative approach with a descriptive type. Data were collected through observation, interviews, and literature reviews. Data were analyzed through data collection, data reduction, data presentation, and drawing conclusions. Data validity was carried out through source triangulation. The results of the study indicate that BK teachers have implemented career guidance through career information services, carried out in stages starting from individual counseling, class guidance, and providing guidance regarding further studies. Furthermore, guidance counselors involve alumni in career guidance activities to broaden students' horizons and knowledge about various further education options and career prospects after graduation. Based on interviews, students' career readiness levels are estimated to be in the range of 50% to 60%. This is evidenced by the fact that after counseling, students are better able to identify themselves and find direction. Therefore, the career development services provided by guidance counselors contribute to and have a positive impact on improving students' career readiness.